The Relationship Between Knowledge, Income, and Consumption Pattern With Ced Events in Pregnant Women - Maulana, Muhammad naufal; Fathurrahman, Fathurrahman; Mas'odah, Siti (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2024)
In Indonesia, there are many cases of Chronic Energy Deficiency (CED), especially those possibly caused by an imbalance in nutritional intake (energy and protein), so that the nutrients the body needs are not fulfilled. The purpose of this study was to determine the relationship between knowledge, income and consumption patterns with the incidence of CED in pregnant women in the working area of the North Kambat Health Center. This research method uses analytic observational with cross sectional design. The population is all pregnant women in the working area of the North Kambat Health Center and the total sample is 82 people. Defendant variables are the incidence of CED in pregnant women and independent variables are knowledge, income and consumption patterns, taken by means of questionnaires and interviews. Connect data using test Rank Spearman. The results showed that 37.8% of respondents experienced CED and 62.2% did not experience CED. As many as 40.2% of respondents have less knowledge and as many as 36.6% of respondents have sufficient knowledge. Income in the category above averages as much as 39% and with categories below the average as much as 61%. The pattern of consumption in the less category is 54.9% and in the good category is 45.1%. It is expected that pregnant women consume a balanced menu of food in an amount that suits their needs.